Kemampuan Membaca Nyaring Siswa Kelas II SD Negeri 11 Banda Aceh - masitrah masitrah; M. Husin; Suci Fitriani (Universitas Syiah Kuala, 2022)
Perusing out loud is an action for educators and understudies to get information, thoughts, and feelings of a writer and voice their writing orally with proper pronunciation and intonation. The ability to read aloud is one of the most important language skills, because it can enrich vocabulary, add information, and provide opportunities for students to listen and imagine. The plan of the issue in this study is